Is It Choice or Is It Bias? Questions About the Harris Survey for The Commonwealth Fund on Managed Care - Pfeiffer, David (Disability Studies Quarterly, 2001)
A major contribution to the debate over managed care in the 1990s was a survey carried out by Louis Harris & Associates for The Commonwealth Fund. It was instrumental in casting doubt on the efficiency and effectiveness of manage care. However, there are fundamental problems with the survey which cast doubt on its results. These problems are discussed.